2009
DOI: 10.2527/jas.2008-1670
|View full text |Cite
|
Sign up to set email alerts
|

Extended field test on the use of visual ear tags and electronic boluses for the identification of different goat breeds in the United States1

Abstract: A total of 295 goats from 4 breeds (Alpine, n = 74; Angora, n = 75; Boer-cross, n = 73; Spanish, n = 73) were used to assess the retention of 3 types of electronic ruminal boluses (B1, 20 g, n = 95; B2, 75 g, n = 100; and B3, 82 g, n = 100) according to breed and feeding conditions. Time for bolus administration, reading with a handheld reader, and animal data recording (goat identification, breed, and bolus type) were registered. Each goat was also identified with 1 flag-button plastic ear tag (4.6 g, 51 x 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…Carne et al (2009a) reported a retention rate of 98.1% for rumen bolus and 91.7% for visual ear tags in different goat breeds at 6 months. In addition, Abecia and Palacin (2014) determined lower retention (63%) and readability (78.2%) rates when compared with the findings in this study for goats identified with electronic leg tags at 6 months after tagging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Carne et al (2009a) reported a retention rate of 98.1% for rumen bolus and 91.7% for visual ear tags in different goat breeds at 6 months. In addition, Abecia and Palacin (2014) determined lower retention (63%) and readability (78.2%) rates when compared with the findings in this study for goats identified with electronic leg tags at 6 months after tagging.…”
Section: Resultsmentioning
confidence: 99%
“…This result for DRE complied with those reported by Caja et al (1999), Carne et al (2011), and Abecia and Palacin (2014) for electronically identified goats. Carne et al (2009a) reported that the use of small transponders causes poor dynamic reading efficiency due to their short reading distance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics affect retention rate and few studies have been conducted with the objective to determine the adequate dimensions and weight of ruminal boluses for goats. However, better results with adult goats have been observed with ruminal boluses weighing 70 g or more (Pinna et al, 2006;Carné et al, 2009a;Carné et al, 2009b;Carné et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…However, high variability has been observed for retention rate of electronic rumen boluses in goats (Pinna et al, 2006;Carné et al, 2009a;Carné et al, 2009b). The objective of this study was to evaluate three identification devices for adult goats reared in semi-intensive system.…”
Section: Introductionmentioning
confidence: 99%